Role of Geographers in the Analysis and Modeling of the Spread of Communicable Diseases (Malaria & COVID-19) in Ambon City: A Spatial Approach for Epidemiological Analysis - Latue, Theochrasia; Latue, Philia; Liwan, Sandy; Manakane, Susan; Rakuasa, Heinrich (International Journal of Multidisciplinary Approach Research and Science, 2023)
This study explores the role of geographers in analyzing the distribution of infectious diseases (malaria and COVID-19) in Ambon City with a spatial approach in epidemiological analysis. The method used in this review is a comparative descriptive study with a qualitative approach using secondary data from relevant sources. This research will review the role of geographers in analyzing and modeling the distribution of infectious diseases (malaria & COVID-19) in Ambon City from previous research. This research integrates geographic and health data to understand the pattern of spread and environmental factors that influence disease. Through case mapping, environmental factor analysis, and modeling of future trends, this research illustrates the important contribution of geographers in infectious disease control and prevention efforts at the local level. Interdisciplinary collaboration plays a key role in this approach, which ultimately supports more informed and effective decision-making in addressing these health challenges.